Avaliação do emprego de diferentes protocolos de antibioticoterapia profilática na expansão rápida de maxila assistida cirurgicamente: um estudo clínico controlado, duplo-cego, randomizado - Souza, Maykel Sullyvan Marinho (2019)
Introduction: Dentofacial deformities affect approximately 2.5% of the population. However, there is not enough data in the literature to estimate the incidence of transverse maxillary discrepancy (TMD) in adult patients. The diagnosis of TMD is based on the analysis of models being articulated in class I of Angle. Once the patient has reached skeletal maturation, the only way to treat TMD is by surgery, more particularly by surgically assisted rapid maxillary expansion (SARME). Like any surgical procedure, the SARME may have a variaty of complications, such as infection. Therefore, it is essential to know its degree of contamination and the ways to prevent it, in particular, through prophylactic antibiotic therapy. The actual need for its use and the most appropriate therapeutic regimen of antibiotics are still grounds for debate in the literature, which is probably due to the lack of randomized clinical trials. Thus, the present study was conducted aiming to compare the effects of different prophylactic antibiotic therapy regimens on infection rates in patients submitted to SARME. Materials and methods: A single-center, randomized, double-blind clinical trial was performed with 23 patients undergoing SARME who were randomly assigned to receive cefazolin 1 g one hour before the procedure (G1) or cefazolin 1 g one hour before the procedure and whithin the first 24 hours postoperatively (G2). The surgical sites were evaluated in the pre- and postoperative periods for the presence of infection according to the criteria of Mangram et al. (1999). Results: 23 patients of both sexes (6 men and 17 women), representing 26% and 74%, respectively, were part of the study. The pain symptom was reported with p = 0.578 in Group I. Edema was observed in the first three evaluations of Groups I and II, but with p <0.05, as well as erythema, fever, abscess and purulent drainage. There was no statistically significant difference between the different antibiotic prophylaxis protocols used in the study, but the mean number of the sum of inflammatory G1 scores (5.67 ± 2.20) was significantly higher than in G2 (0.36 ± 0.28 ) (p = 0.035). Conclusion: Based on the patient selection criteria and the results of the study, it was concluded that a single dose of cefazolin 1 g one hour before the procedure is sufficient to prevent infection in patients undergoing SARME.